2016
DOI: 10.1021/acs.jafc.6b03561
|View full text |Cite
|
Sign up to set email alerts
|

Pod Mildew on Soybeans Can Mitigate the Damage to the Seed Arising from Field Mold at Harvest Time

Abstract: Seedpods are the outermost barrier of legume plants encountered by pests and pathogens, but research on this tissue, especially regarding their chemical constituents, is limited. In the present study, a mildew-index-model-based cluster analysis was used to evaluate and identify groups of soybean genotypes with different organ-specific resistance against field mold. The constituents of soybean pods, including proteins, carbohydrates, fatty acids, and isoflavones, were analyzed. Linear regression and correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…In our recent studies on FM in preharvest soybean seed, we found that mildew resistance was significantly correlated with the seed coat color and that soybean seeds with dark coats showed higher field mold resistance [ 13 ]. Although the obtained evidence confirmed that the antimycotic constituent primarily originated from the medium-polarity fraction [ 14 ], we believe that new functional constituents, especially polysaccharides, are contained in the wasted high-polarity, water-soluble fraction of the black soybean seed coat. In the present study, a three-level, three-factor Box-Behnken design was combined with response surface methodology (RSM) to optimize the extraction conditions for obtaining the maximum yield of BSCPs.…”
Section: Introductionmentioning
confidence: 76%
“…In our recent studies on FM in preharvest soybean seed, we found that mildew resistance was significantly correlated with the seed coat color and that soybean seeds with dark coats showed higher field mold resistance [ 13 ]. Although the obtained evidence confirmed that the antimycotic constituent primarily originated from the medium-polarity fraction [ 14 ], we believe that new functional constituents, especially polysaccharides, are contained in the wasted high-polarity, water-soluble fraction of the black soybean seed coat. In the present study, a three-level, three-factor Box-Behnken design was combined with response surface methodology (RSM) to optimize the extraction conditions for obtaining the maximum yield of BSCPs.…”
Section: Introductionmentioning
confidence: 76%
“…Nowadays, various analytical platforms were widely used in the study of soybean metabolism and corresponding molecular mechanism elucidation (Chai et al, 2012;Lee et al, 2017;Silvente, Sobolev, & Lara, 2012;Sun, Feng, & Ort, 2014;Wu et al, 2008). However, metabolomics researches on soybean mainly focus on seed and leaf rather than pod, which was demonstrated as an important organ in the FM resistance (Liu et al, 2016). Single solvent is widely used in different plant tissue and organs (Benkeblia, Shinano, & Osaki, 2007;Chebrolu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Grain fungi can be divided into two large categories, field and storage molds, based on the location of the outbreak (Liu et al, 2016). Storage fungi can grow at low water activity, which occurs readily under a high-temperature (25–30°C) and humid environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent research demonstrated a potentially important function of soybean pods in FM resistance at the phytochemical level (Liu et al, 2016). With increases in the contents of infection components, such as proteins, carbohydrates, and fatty acids, the MIP increased and the MIS decreased, demonstrating indirectly that pod mildew can help mitigate the corresponding seed mildew to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation